Respuesta :
each term is 2 times the previous
geometric series
an=a1(r)^(n-1)
an=nth term
a1=first term
n=which term
r=common ratio
common ratio is 2
first term is 7
n=10
so
7(2)^(10-1)
7(2)^9
last option is the answer
geometric series
an=a1(r)^(n-1)
an=nth term
a1=first term
n=which term
r=common ratio
common ratio is 2
first term is 7
n=10
so
7(2)^(10-1)
7(2)^9
last option is the answer
Answer:
7•2^9
Step-by-step explanation:
This is a geometric sequence, since each term is found by multiplying the previous term by 2.
The explicit formula for a geometric sequence is given by
[tex]a_n=a_1 \times r^{n-1}[/tex], where a₁ is the first term and r is the common ratio, and n is the term number.
For our sequence, the first term is 7. The common ratio is 2. This gives us
[tex]a_n=7 \times 2^{n-1}[/tex]
Since we want the 10th term,
[tex]a_{10}=7 \times 2^{10-1}\\\\=7 \times 2^9[/tex]